The Impact of a Training Program Based on Next-Generation Science Standards on Scientific Inquiry - Eman Najjar; Wajeeh Daher (MDPI AG, 2023)
The Next-Generation Science Standards (NGSS) are standards concerned with K-12 grades. This study aimed to identify the impact of a training program based on Next-Generation Scientific Inquiry (NGSI) through training 30 science teachers and investigating the training impact on teachers' use of inquiry in their teaching. The study attempted to answer the following question: What is the impact of a training program based on the NGSS on the inquiry practices of primary school science teachers? The study's data collection tools included two focus groups and nine semi-structured interviews. Data analysis utilized the thematic analysis framework. The research results showed an impact of the training program on the inquiry practices of teachers via changes in the teachers' roles: the teacher became a facilitator and motivator through planning her/his activities efficiently. Students in the training program's science classroom developed into researchers and scientists who autonomously acquired their knowledge.